The Role of Libraries in Improving Digital Literacy and Preventing Misinformation Among Students - Riyanti, Apriani (Bibliogia, 2025)
The development of digital technology presents challenges for students in accessing valid information while increasing the risk of exposure to misinformation. This study aims to describe the role of libraries in improving digital literacy and their efforts to prevent misinformation among students. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. Research informants include students as users of library services and librarians as service providers. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results show that libraries play a strategic role in supporting students' digital literacy by providing access to verified academic sources, digital literacy training, and facilitation by librarians. In terms of preventing misinformation, libraries provide education on information verification, provide valid content, and conduct information literacy campaigns. Despite challenges such as limited resources and low student participation, libraries still have opportunities to develop innovative digital services, strengthen collaboration with lecturers, and optimize digital literacy programs.